My tajwid mobile application - Muhammad Nasrullah, Rosli (2015)
Mobile technology has nowadays become trend in various fields, either in business, education, health, engineering, etc. The need of mobility in accomplishing work is increasing as the technology created more advanced mobile devices that are capable in multitasking such as the smartphones. Tajweed program application for the Android operating system is an application program that provides the teaching of reading and understanding the Tajweed knowledge. There also quiz given to analyzing the understanding of the learning process. Hopefully with the e-learning program Tajweed give new source to gain knowledge especially in enhancing recitation process in Quran. Tajweed application program provides outstanding results to the public, because the system content is accurate and give priority to efficiency and effectiveness. Some of them are people who have used the mobile applications program based. So this is an exciting opportunity that can be used to assist parents or Quran teachers to teach Tajweed.